Efficacy of chlorpropham (CIPC) alternatives on suppressing sprouting of ware potato tubers stored at ambient tropical temperatures - Murigi, Winnie Wanjiku; Nyankanga, Richard Ombui (Journal of Postharvest Technology, 2018)
High postharvest losses are a major constraint to long term storage of potato in Kenya. Cold storage is not feasible due to the high cost and lack of facilities. Use of sprout suppressants could be an attractive proposition. However, sprout-preventing chemicals, such as Chlorpropham (CIPC) negatively impact the environment and human health. This study evaluated the efficacy of two alternative sprout suppressants, Peppermint oil (PPO) and 1, 4 Dimethylnaphthalene (DMN) using three potato cultivars with varying dormancy stored under ambient conditions. After 24 weeks of storage, CIPC suppressive effects was 100% on the three cultivars whereas the non-treated tubers had 100% sprout emergence by sixth (short dormancy), twelfth (medium dormancy), fourteenth (long dormancy) weeks of storage. Inhibition by DMN and PPO varied with cultivars, but were significantly (P<0.05) better than the non-treated tubers. PPO inhibited sprout development for 18 weeks on medium and long dormancy cultivars and 14 weeks on short dormancy cultivar. DMN treatments did not prolong storage in short and medium dormancy cultivars but it greatly reduced sprout growth but not as effective as peppermint. In long dormancy cultivar, DMN equalled the effectiveness of CIPC. The study showed that DMN and peppermint oil could be effective sprout suppressant alternatives to CIPC under tropical ambient conditions and useful for resource-constrained potato farmers.